Surf's up - Jenkins, Chris; Addario, Lisa.; Darren, Christian; Rhymer, Don.; Brannon, Ash.; Buck, Chris; Jenkins, Christopher; LaBeouf, Shia, 1986-; Bridges, Jeff, 1949-; Deschanel, Zooey, 1980-; Heder, Jon, 1978-; Woods, James, 1947-; et al. (Culver City, Calif. : Sony Pictures Home Entertainment, 2007)
Teenage Rockhopper penguin Cody Maverick is an up-and-coming surfer who is about to enter his first pro competition. Followed by a documentary crew to film his experiences, Cody leaves Antarctica for the warmer climes in order to surf in the Big Z Memorial Surf Championship covered by the SPEN network. His hero, champion surfer Big Z, has been gone for ten years, and Cody wants to win the championship in his memory.
DVD release of the 2007 motion picture.
Cinematographer, Andres Martinez ; editor, Ivan Bilancio ; music, Mychael Danna ; production designer, Paul Lasaine ; animators, John Clark ... [et al.] ; visual effects supervisor, Rob Bredow.
Voices: Shia LaBeouf, Jeff Bridges, Zooey Deschanel, Jon Heder, James Woods, Diedrich Bader, Mario Cantone.
MPAA rating: PG.
DVD ; Region 1 ; widescreen presentation ; Dolby Digital.
Closed-captioned.
Keywords: Penguins -- Fiction -- Juvenile films; Surfers -- Fiction -- Juvenile films; Surfing -- Fiction -- Juvenile films; Friendship -- Fiction -- Juvenile films; Sports tournaments -- Fiction -- Juvenile films; Penguins -- Fiction; Surfers -- Fiction; Surfing -- Fiction; Friendship -- Fiction; Sports tournaments -- Fiction; Documentary films -- Production and direction -- Fiction -- Juvenile films; Documentary films -- Production and direction -- Fiction; Surfing films; Sports films; Films for the hearing impaired; Comedy -- Animation -- Feature; Sports -- Animation -- Feature; Animal -- Animation -- Feature; Feature films; Animated films; Comedy films